Design of Alerting System for Beyond Visual Line of Sight Operational Cargo Delivery UAV - Sonaria, Enita; Jenie, Yazdi Ibrahim (WARTA ARDHIA, 2023)
The development of drones is now crucial to many industries, investors, and governments as they are more cost-effective and efficient in various industries, such as filmmaking, consumer, and tourism. They can also be used in various fields, such as agriculture, meteorology, construction, logistics, and conservation. Beyond Visual Line of Sight (BVLOS) technology enables drone operations to perform missions more accurately as it allows them to be operated in a wider angular range. BVLOS includes the use of advanced technologies and systems to monitor drones and ensure they comply with regulations. As such, BVLOS can be used to optimise marine cargo drone operations. In addition, the Ground Control System (GCS) is used by multi-UAV systems to remotely monitor drone performance. This enables advancements in navigation and autonomous technologies that can be utilised in the maritime sector. However, the operation of cargo delivery UAVs, especially those operated as multi-UAVs, requires a surveillance system supported by a qualified warning system. One of them is a warning system that will appear when the UAV approaches the boundary of the area of operation that has been set at the beginning. The warning system aims to improve safety and security because by warning UAVs approaching or entering restricted or sensitive areas, this system can prevent unauthorised access or accidents, ensuring the safety and security of the area and the UAV itself. In addition, it improves efficiency and reduces costs where the warning system can help UAVs avoid entering prohibited or unauthorised locations, improving efficiency, and reducing costs associated with re-routing or returning to home. For this reason, in this research, the design of a warning system for UAVs approaching the boundary of the operating area is performed and shown through simulation. In this research, a two-level alert system was designed and simulated that is triggered when the UAV approaches the boundary of the specified operation area to enable the operation supervisor to perform safety procedures in response to mitigate potential risks.